The Effect of Product Bundling Strategy, Countdown Timer Urgency, and Social Proof on Interactive Responses to Live Streaming as Alpha Gen Moderation Variables on Scora Products in Bandar Lampung - Dela Merais; Euis Mufahamah; Hamida Nur Rahmawati (International Journal of Economics, Commerce, and Management, 2026)
This study aims to analyze the effect of product bundling strategies, countdown timer urgency, and social proof on the interactive responses of Generation Alpha consumers toward Scora skincare products in Bandar Lampung, with live streaming as a moderating variable. Interactive responses in this study include comments, questions, likes, and purchase actions during live streaming sessions. This research employs a quantitative approach, with data collected through ques-tionnaires. The sample consists of 300 Generation Alpha respondents in Bandar Lampung who have watched Scora’s live streaming promotions. Data analysis techniques include multiple linear regression analysis and Moderated Regression Analysis (MRA). The results indicate that product bundling strategies, countdown timer urgency, and social proof have a positive and significant effect on interactive responses, both partially and simultaneously. However, the moderation test results reveal that live streaming does not moderate the relationship between product bundling strategies, countdown timer urgency, and social proof on interactive responses. These findings suggest that although live streaming serves as a primary promotional medium, it does not necessarily strengthen the influence of marketing strategies on Generation Alpha’s in-teractive responses. This study is expected to provide practical insights for local skincare brands in developing more effective digital marketing strategies through live streaming commerce.